2020
DOI: 10.1038/s41598-020-68066-3
|View full text |Cite
|
Sign up to set email alerts
|

Taphonomy and chronosequence of the 709 ka Kalinga site formation (Luzon Island, Philippines)

Abstract: The recently described site of Kalinga in the Philippines adds to our understanding of Early-Middle Pleistocene hominin behaviour. Yet, disentangling the natural from the anthropogenic modifications that have taken place in such an old archaeological site is challenging. In this paper we use a set of taphonomic tools at hand to rectify the distortion made by natural processes during the formation of the Kalinga site. From the description of the ribs completeness, surface damages and scattering in the excavatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…A partial skeleton of Rhinoceros philippinensis von Koenigswald, 1956 (Figure S1) was recently discovered at Kalinga site in Northern Luzon from a 709±68 ka archaeological layer. Stone tools were recovered together with the skeleton and several skeletal elements exhibited evidence of butchery (Ingicco et al, 2018(Ingicco et al, , 2020. This early Middle Pleistocene individual considerably adds to the knowledge of Philippine rhinocerotid species, as its hypodigm was restricted to a few fossil teeth without any clear stratigraphic context, recovered from different islands in the archipelago (von Koenigswald, 1956;Bautista, 1995).…”
Section: Introductionmentioning
confidence: 92%
“…A partial skeleton of Rhinoceros philippinensis von Koenigswald, 1956 (Figure S1) was recently discovered at Kalinga site in Northern Luzon from a 709±68 ka archaeological layer. Stone tools were recovered together with the skeleton and several skeletal elements exhibited evidence of butchery (Ingicco et al, 2018(Ingicco et al, , 2020. This early Middle Pleistocene individual considerably adds to the knowledge of Philippine rhinocerotid species, as its hypodigm was restricted to a few fossil teeth without any clear stratigraphic context, recovered from different islands in the archipelago (von Koenigswald, 1956;Bautista, 1995).…”
Section: Introductionmentioning
confidence: 92%
“…The relatively small flakes (< 100 mm in length) remain mostly unretouched and were mainly manufactured from siliceous rocks, such as chert, flint, or quartzite, as well as igneous rocks. The assemblages included cores and hammerstones, suggesting that at least some of the flakes were manufactured at the site (Ingicco et al, 2018;Ingicco et al, 2020). Microscopic usewear analysis conducted by one of the authors (AP) indicated that some tools may have been used in butchering the rhinoceros and for other uses, e.g., processing of plants.…”
Section: Materials Culturementioning
confidence: 99%